2015
DOI: 10.21608/jppp.2015.75786
|View full text |Cite
|
Sign up to set email alerts
|

COMPARATIVE MOLLUSCICIDAL ACTIVITY OF ABAMECTIN AND METHOMYL AGAINST Eobania vermiculata (Müller) AND Theba pisana (Müller

Abstract: The molluscicidal activity of abamectin were assessed compared with methomyl against the most two abundant snail species brown garden snail (BGS) Eobania vermiculata and white garden snail (WGS) Theba pisana under laboratory conditions. The results indicated that LC50 values of methomyl were almost equal LC50 values of abamectin indicating more molluscicidal potency of abamectin and methomyl. Results also revealed a complete consistency of correlation between the LC50 values and exposed time intervals. The hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Although all tested pesticides considered insecticides, these pesticides used as molluscicides successfully. The previous studies confirmed that abamectin was more effective against the chocolate snail (Essawy et al 2009;Abdallah et al 2015;Hemmaid et al 2017). Using of imidacloprid and fipronil as ovicides was a very effective action against the hatchability of E. vermiculata eggs.…”
Section: Discussionmentioning
confidence: 60%
“…Although all tested pesticides considered insecticides, these pesticides used as molluscicides successfully. The previous studies confirmed that abamectin was more effective against the chocolate snail (Essawy et al 2009;Abdallah et al 2015;Hemmaid et al 2017). Using of imidacloprid and fipronil as ovicides was a very effective action against the hatchability of E. vermiculata eggs.…”
Section: Discussionmentioning
confidence: 60%
“…There is an information of the toxic effects of ABM against land snails, where it had lethal toxic actions on the freshwater snails, Physa acuta [40], Biomphalaria alexandrina [41], land snails: Monacha contiana [42] and M. obstructa [43]. In addition, ABM was found to be more toxic on chocolate snail Eobania vermiculata [21,[44][45]. On the same species, assessment of pesticides: indoxacarb, ABM, and spiromesifen for 24 h obtained that, indoxacarb was the most toxic, followed by ABM and spiromesifen.…”
Section: Discussionmentioning
confidence: 99%
“…The avermectin B1 (Abamectin) proved its ability to manage different pests as an acaricide [16,21], insecticides [22], nematicide [10,23] and Molluscicide [24][25][26]. Meanwhile, abamectin was applied in many different methods such as soil treatment, seed treatment, injection in to plant stem and seedling root dip (Table 1) (Figure 1).…”
Section: The Effi Cacy Of Abamectin On Plant Parasitic Nematodesmentioning
confidence: 99%